Controlled carbonization of microplastics loaded nano zero-valent iron for catalytic degradation of tetracycline. (September 2022) - Sun, Ruirui; Yang, Jiapeng; Huang, Rong; Wang, Chongqing
Abstract: Nano zero-valent iron loaded porous carbon derived from microplastics was designed as heterogeneous catalyst for degradation of persistent organic pollutants. Controlled carbonization of microplastics with molten salt was conducted to tune the morphology of carbon product. Controlled carbonization induces higher carbon yield (from 17.73% to 52.24%) and larger surface area (from 403.72 m 2 /g to 601.82 m 2 /g). The catalyst (Fe/MMPC) was characterized by Raman, Fourier transform infrared spectroscopy, X-ray diffraction, X-ray photoelectron spectroscopy, and scanning electron microscope. Loading nano zero-valent iron onto porous carbon are verified in the catalyst. The process factors including Fe/MMPC dosage, H2 O2, pH, anions, and temperature were studied to estimate the catalytic performance. Tetracycline degradation (81.8% within 10 min) is effectively obtained in the Fe/MMPC and H2 O2 system. The apparent rate constant is 0.1311–0.2999 min −1 under different temperature, and the activation energy of catalytic process is 22 kJ/mol. Pollutants including rhodamine B, p -nitrophenol, and butylxanthate are efficiently degraded in the catalytic system. The predominant species of catalytic reactions are hydroxyl radicals, which are mainly produced from H2 O2 activation enhanced by zero-valent iron in Fe/MMPC. This work offers an innovative strategy for microplastic management and wastewater treatment. Graphical abstract: Image 1 Highlights: Carbon substrate was fabricated by controlled carbonization of microplastic. Nano zero-valent iron loaded porous carbon was used as heterogeneous Fenton catalyst. Effectively degrading tetracycline was proved by high rate constant and low activation energy. Degradation of POPs including Rhodamine B, p -nitrophenol, and butylxanthate was verified. Catalytic mechanism was revealed associated with multiple characterizations and analysis.